ONA TILI VA O`QISH SAVODXONLIGI FANINI O‘QITISHDA O‘YINLARDAN FOYDALANISH - Turakulova Hilola Yax'yoyevna; Kudratova Zilola Samaraliyevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: In this article, you will learn how to engage younger students in mother tongue science and reading literacy through games, and how to quickly teach new topics. Quick guide on how to play.